225 Assessment of Well-being after Stroke. (16th September 2019) - Donaghy, Lisa; McAteer, Claire; Morrison, Laura; O'Connor, Marie; Dolan, Eamon
Abstract: Background: Studies have shown that people who have had a stroke are more likely to experience a lower sense of overall well-being, including cognitive impairment, mental health issues, and physical function, than similarly aged people 1 . Cognitive impairment and memory dysfunction following stroke diagnosis can significantly impact patients' quality of life 2 . The aim of this study was to identify how stroke has affected patients at a university teaching hospital stroke clinic in terms of memory, mood and how they are managing at home. Methods: Thirty anonymous patient questionnaires were completed at a stroke clinic in April 2019. 100% response rate was obtained. Questions included how patients found their mood and memory, and how they were managing at home following their stroke diagnosis. Results: 50% of respondents reported having memory difficulties post-stroke. 57% described low mood since their stroke. 43% required additional help following discharge home, with 69% of this extra help coming from family support. 13% felt they need more help at home than they currently have, with one of these four respondents awaiting a home care package. 20% of patients received further rehabilitation as an outpatient on discharge. Conclusion: This study highlights significant concerns from patients following stroke with regard to their memory and mood. This emphasises the importance of formal assessment of mood and memory both during admission and on an ongoing basis post discharge. A significant proportion of patients required additional help at home with family members providing the majority of this support.